The Rational Options For Investors To Choose Star Hotel Investments In Surabaya Indonesia - Sugito, Sugito; Budiyanto, Budiyanto; Suwitho, Suwitho (Publisher Cv. Inara, 2024)
Surabaya and Pandemic conditions that have occurred before, hampering the level of hotel occupancy in Surabaya and affecting hotel revenue resulted in several hotels streamlining all activities to minimize operational costs can minimize losses due to lack of occupancy due to Pandemi Covid 19, the interest of investors to invest in the star hotel business in the city of Surabaya. Conditions of Phenomenon Contractions for What Study can make investors remain optimistic and dare to do the star hotel business in Surabaya, (BPD PHRI East Java, 2021). Decision Making Theory's action, becoming the social capital of investors contributed to the decision to invest in hospitality business, mushroomed new hotels in the city of Surabaya. The highlight of PHRI urged the Surabaya City Government to take steps to limit the construction of a new star hotel (moratorium), in order to prevent overloop supply and unfair business competition in the star hotel industry in the city of Surabaya.The theory of irrational and rational actions explains why people learn to believe, for various levels and in certain contexts. The learning process takes place through repeated interactions and by looking at the interaction of others. shows that the efficient way to explain human actions is by assuming individuals to act for a series of reasons (Ritzer and Smart, 2014: 757). The study of this research uses a transdental phenomenological approach, putting an understanding of Fonemena to build the meaning of the experience of the object of the informants of the starred hospitality industry in Surabaya, namely investors and relations near investors. What is the background and motivation of investors in choosing a hotel business, how is the process and view of the realization of hotel business by investors, what is the view of investors in managing hotel business and the impact of hotel business on other investor businesses. Previous business expertise, investors with previous business experience may find the possibility of investing in attractive hotel industries, long -term property investment, hotel industry is often a promising industry. The value of hotel assets is often high, and its value tends to increase from time to time, media actualization, for some investors, investing in the hotel industry can be a way to achieve self -actualization. They could have wanted to be involved in manufacturing typical and attractive property because they have personal interest in the hospitality sector, increase customer confidence, investors who have a strong reputation or have achieved success in other industries can utilize investment in the hospitality industry as a way to increase customer confidence.